Maternal dietary patterns and acute leukemia in infants: results from a case control study in Mexico - Muñoz-Aguirre, Paloma; Denova-Gutiérrez, Edgar; Pérez-Saldivar, María Luisa; Espinoza-Hernández, Laura E.; Dorantes-Acosta, Elisa M.; Torres-Nava, José R.; Solís-Labastida, Karina A.; Paredes-Aguilera, Rogelio; Velázquez-Aviña, Martha M.; Espinosa-Elizondo, R. Martha; Miranda-Madrazo, M. Raquel; González-Ávila, Ana Itamar; et al. (Frontiers in Nutrition, 2023)
Childhood cancer is the leading cause of disease-related mortality among children aged 5-14 years in Mexico, with acute leukemia being the most common cancer among infants. Examining the overall dietary patterns allows for a comprehensive assessment of food and nutrient consumption, providing a more predictive measure of disease risk than individual foods or nutrients. This study aims to evaluate the association between maternal dietary patterns during pregnancy and the risk of acute leukemia in Mexican infants.A hospital-based case-control study was conducted, comparing 109 confirmed acute leukemia cases with 152 age-matched controls. All participants (≤24 months) were identified at hospitals in Mexico City between 2010 and 2019. Data on a posteriori dietary patterns and other relevant variables were collected through structured interviews and dietary questionnaires. Multivariate logistic regression was employed to estimate the association between maternal dietary patterns during pregnancy and the risk of acute leukemia in infants.The "Balanced & Vegetable-Rich" pattern, characterized by a balanced consumption of various food groups and higher vegetable intake, exhibited a negative association with acute leukemia when compared to the "High Dairy & Cereals" Pattern (adjusted odds ratio [OR] = 0.51; 95% confidence interval [CI]: 0.29, 0.90). We observed that mothers who gave birth to girls and adhered to a healthy dietary pattern during pregnancy exhibited significantly lower odds of their children developing AL compared to those who gave birth to boys (OR=0.32 (95% CI 0.11, 0.97). Our results underscore the significance of maternal nutrition as a modifiable factor in disease prevention and the importance of prenatal health education.